Corrections to “An Overview of Hand-Drawn Diagram Recognition Methods and Applications” - Vanita Agrawal; Jayant Jagtap; Mvv Prasad Kantipudi (IEEE Access, 2024)
Presents corrections to the paper, (Corrections to “An Overview of Hand-Drawn Diagram Recognition Methods and Applications”).